Inserção de professores iniciantes no campo profissional : um estudo de caso na escola básica - Simon, Marinice Souza (2013)
This work inserts itself in the line of the research Formation, Policies and Practices in Education of a qualitative mark and it has thematic the problematical of the teaching trajectory in its initial stage difficulties in professional insertion and support actions found in the school to the new teacher. The methodology used for the development of the research sets up a Study of Case in the search to analyses the reality, to talk and to participate of the reflections of the interlocutors with the purpose to understand the teaching s thoughts in the beginning of career. The subjects are beginning teachers of Basic Education with till five years of actuation, and supervisors who work with them. For the collection of information are used semi structured interviews and the unsystematic observation. The study aims to contributes for the deepening of the thematic related to the beginning teachers and their professional insertion with the thesis of since the initial training course until the school which welcomes the teachers in the beginning career, it is necessary the structure of mechanisms of pedagogical and personal support, for this professional can be better prepared to overcome the obstacles and build the network relationships which will strengthen his practices. The bibliographical reference collects theoretics and authorships, among them point out: Vieira Pinto (1969), Freire (1987), Santos (1989, 2005), Garcia (1998,1999, 2009), Rios (2008), Nóvoa (1992, 1999), Contreras (2002), Tardif (2000, 2002, 2005), Assmann (2007), Pimenta (2008), Fernandes (1999, 2003, 2008, 2009).The carried information out is carefully considered constituting a dialog between the studied theories and the investigated reality contributing for the formulation of the ideas about the possibilities of insertion of professional development of beginning teachers in the Basic School scenery.